2020
DOI: 10.1002/aic.16229
|View full text |Cite
|
Sign up to set email alerts
|

Viscoelastic surfactant fluids filtration in porous media: A pore‐scale study

Abstract: We investigated the flow of viscoelastic surfactant (VES) solutions, an important type of fracturing fluids for unconventional hydrocarbon recovery, through a divergingconverging microfluidic channel that mimics realistic unit in porous media. Newtonian fluid and viscoelastic hydrolyzed polyacrylamide (HPAM) solution were used as control groups. We vary Deborah numbers (De) up to 61.2, and found that the flow patterns of HPAM and VES solutions become very different once De ≥ 6.12. This is attributed to differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…Recently, nanofluids with high thermostability and interfacial activity attract more and more attention (Noreen et al 2016;Lu et al 2017). Previous studies have also indicated that nanofluids have shown the application potential in drag reduction, chemical flooding, filtration reducer and so on (Zhao et al 2018a, b;Ramesh and Prabhu 2011;Soltanipour et al 2016;Zhong et al 2011;Mu et al 2010;Zhao et al2018a, b;Hwang et al 2008;Dai et al 2020;Li et al 2020;Zhao et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, nanofluids with high thermostability and interfacial activity attract more and more attention (Noreen et al 2016;Lu et al 2017). Previous studies have also indicated that nanofluids have shown the application potential in drag reduction, chemical flooding, filtration reducer and so on (Zhao et al 2018a, b;Ramesh and Prabhu 2011;Soltanipour et al 2016;Zhong et al 2011;Mu et al 2010;Zhao et al2018a, b;Hwang et al 2008;Dai et al 2020;Li et al 2020;Zhao et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The success of this operation depends on whether the fracturing fluid has satisfactory rheological properties and a suitable proppant carrying capacity . Many novel fracturing fluids, such as viscoelastic surfactants (VESs), slick water, supramolecular polymers, energized fluids, and supercritical carbon dioxide (CO 2 ), have been designed and developed through oilfield chemistry research. Nevertheless, traditional guar-based linear or cross-linked fracturing fluids are still the most commonly used fluids in oilfields due to their desirable performances and low costs. …”
Section: Introductionmentioning
confidence: 99%